2016
DOI: 10.14326/abe.5.32
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Determining Scale Parameters in a Hemodynamic model incorporating Cardiac Cellular Contraction model

Abstract: Scale parameters are used to combine two or more models in different scales into one integrative model. One of the crucial issues in the research eld of biosimulation in hemodynamics is how to determine the scale parameters in comprehensive hemodynamic models comprising a cardiac cellular contraction model and a circulation model. In this report, we propose a method for determining the scale parameters using mathematical equations derived from the shape of the left ventricle (LV), which is assumed to be a hemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…In this research, a simplified hemodynamic model proposed by our group [49, 45] was used for mathematical analysis. The model was constructed from a circulation model, a LV geometry model, and a muscle contraction model.…”
Section: Model and Definitionsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this research, a simplified hemodynamic model proposed by our group [49, 45] was used for mathematical analysis. The model was constructed from a circulation model, a LV geometry model, and a muscle contraction model.…”
Section: Model and Definitionsmentioning
confidence: 99%
“…Utaki et al [49, 45] used the following reported data to define the relation between R ιυ and L . Rodriguez et al [31] also measured the time course of canine LV sarcomere length.…”
Section: Model and Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…We thus introduced a scale factor, K s , which is multiplied only to F b to adjust cellular contraction stress. K s was determined using the method proposed by Utaki et al [27] which resulted in K s = 6.65. Finally, total muscle stress F [mN/mm 2 ] as used in Eq.…”
Section: Cardiac Cellular Contraction Modelmentioning
confidence: 99%